(untitled) (DARYAFT, 2023)
Literature generally and fiction particularly are permanent features of human life. Different types of story, classic and modern, varies in their themes, technique as well as their way of presentation. These variations based on changing values of human beings with respect to their age. This article analyses the social background of story and its changing types. There are some interesting aspects of story genres regarding the diversifications of old and modern way of human life as well as prospective social changes. These dimensions are discussed here in light of profane life. The core focus is the Modern Urdu short story.